2015
DOI: 10.12809/hkmj144363
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular stenting in the management of malignant superior vena cava obstruction: comparing safety, effectiveness, and outcomes between primary stenting and salvage stenting

Abstract: Objective: To compare the safety, effectiveness, and outcomes of primary stenting and salvage stenting for malignant superior vena cava obstruction. Design: Case series with internal comparison.Setting: Regional hospital, Hong Kong. Patients:A total of 56 patients with malignant superior vena cava obstruction underwent 59 stentings from 1 May 1999 to 31 January 2014. Patients' characteristics, procedural details, and outcomes were retrospectively reviewed. Of the 56 patients, 33 had primary stenting before con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…Between 10% and 60% of patients with SVC obstructions exhibit SVC and bilateral brachiocephalic vein obstruction. [3,12,13] At the present case series, 2 patients (40%) presented with obstruction of SVC and bilateral brachiocephalic veins, and this result is comparable to the previous studies. [3,12,13] However, treatment of obstruction of SVC and bilateral brachiocephalic veins is not complicated, and unilateral stent insertion can achieve clinically successful outcomes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Between 10% and 60% of patients with SVC obstructions exhibit SVC and bilateral brachiocephalic vein obstruction. [3,12,13] At the present case series, 2 patients (40%) presented with obstruction of SVC and bilateral brachiocephalic veins, and this result is comparable to the previous studies. [3,12,13] However, treatment of obstruction of SVC and bilateral brachiocephalic veins is not complicated, and unilateral stent insertion can achieve clinically successful outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…These symptoms usually reduce patients’ quality of life for the remaining period of time during which they survive. [3,4] Patients with CMASO may have more serious illness condition than patients with only airway or SVC obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Stenting has largely replaced radiation therapy as the first line procedure for managing malignant SVCS, due to its immediate nature, high success rate, and the retained possibility to attempt alternative therapies [4,10,12]. The only study to specifically examine the impact of stenting as a first-line procedure was a retrospective study of 56 malignant SVCS patients by Leung et al [41]. They found that patients who received stenting at initial presentation had significantly increased survival over patients who received stenting after the failure of traditional treatments, but found no significant difference in success rate, procedure time, symptom relief, complication rate or re-intervention rate.…”
Section: Discussionmentioning
confidence: 99%
“…Stenting was attempted as the first-line procedure for treatment of malignant SVCS in 4/54 studies, comprising 202 patients [17,20,22,40]. One further study retrospectively investigated a cohort of 56 malignant SVCS patients, with 33 patients undergoing stenting at initial presentation before chemoradiotherapy and 23 only after the failure of chemoradiotherapy [41]. Technical Success…”
Section: Previous Treatments Attemptedmentioning
confidence: 99%
See 1 more Smart Citation